The Effect of Using Flower Writing Strategy on Students’ Writing Skills of First Grade Students in Vocational High School - Raehan Anwar; Asma Alhusna; Rahma Dania; Dwi Megista Putri (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This study investigated the effectiveness of the Flower Writing Strategy in improving tenth-grade students’ writing skills. Employing a quantitative approach with a pre-experimental one-group pre-test and post-test design, the research was conducted at a vocational high school in Padang. A total of 35 students from Class X Culinary 1 were selected as the sample through purposive sampling. Data were collected using a writing test administered before and after the treatment. The collected data were analyzed using a t-test to examine the research hypothesis. The results revealed that the calculated t-value (3.442) exceeded the critical t-table value at the 0.05 significance level (1.692), indicating a statistically significant difference between students’ pre-test and post-test scores. Consequently, the alternative hypothesis (Hₐ) was accepted, while the null hypothesis (H₀) was rejected. These findings demonstrate that the Flower Writing Strategy has a significant positive effect on students’ writing skills. The study suggests that this strategy can serve as an effective instructional approach to enhance writing performance in EFL classrooms, particularly at the vocational high school level.